Foundcare - ALMEIDA, Arthur Alexandre Queiroz de; SOUSA, Geovanna Silva; SÁ, Italo Carvalho; OLIVEIRA, Jefferson Matheus Gonçalves de; MOURA, João Vitor Viana de; SILVA, Ruan de Luna (166, 2024)
O presente trabalho propõe a criação de um WebApp denominado FoundCare, com o objetivo de conectar pacientes que necessitam de cuidados domiciliares a profissionais de saúde qualificados. A plataforma busca resolver problemas recorrentes na busca por cuidadores, como falta de acessibilidade, confiança e centralização de informações. A proposta do FoundCare visa garantir uma experiência intuitiva para usuários, oferecendo ferramentas que permitem personalizar a seleção de profissionais com base em especialização, avaliações e preferências específicas. Além disso, a plataforma também abre oportunidades de renda para cuidadores e profissionais da saúde. O desenvolvimento do WebApp combina tecnologias como React Native (Front-End), Laravel com API REST (Back-End) e MySQL (Banco de Dados), utilizando autenticação avançada para assegurar segurança e confiabilidade. O design foi orientado por pesquisas de campo que identificaram necessidades de pacientes e cuidadores, garantindo a adequação às demandas do mercado. Com o aumento da demanda por serviços de homecare, especialmente devido ao envelhecimento populacional, o FoundCare se posiciona como uma solução inovadora, promovendo dignidade, segurança e eficiência no acesso a cuidados domiciliares.

This study addresses the critical need for quality home healthcare services in Brazil, particularly for individuals recovering from health issues or facing mobility challenges. The research identifies the difficulties patients and families encounter in finding qualified caregivers, often relying on informal networks and lacking access to adequate information. Our primary objective is to develop a user-friendly web application that connects patients with specialized healthcare professionals, ensuring safety, empathy, and personalized care. We explore the current landscape of home healthcare, highlighting the lack of centralized platforms and the challenges in accessing reliable services. By conducting quantitative and qualitative research, we gather insights into patient needs, caregiver qualifications, and market demands. The findings indicate a significant opportunity for a centralized web application that integrates various healthcare services, promotes user engagement, and facilitates efficient caregiver selection based on experience and user reviews. The proposed web application aims not only to streamline the process of finding caregivers but also to empower healthcare professionals by providing a platform for earning additional income. This innovation seeks to enhance the dignity and quality of care for patients, particularly as Brazil's elderly population continues to grow. Our research emphasizes the importance of developing a reliable tool that addresses the ongoing challenges in home healthcare, ultimately contributing to a more effective and compassionate healthcare system.
Foundcare
Keywords: Plataforma digital; Inovação; Cuidados domiciliares de saúde; Tecnologias da saúde; Serviços de saúde; Informação e Comunicação